The effect of adding red dragon fruit peel extract (Hylocereus polyrhizus) in feed to increase color brightness in guppy fish (Poecilia reticulata) - Maulida Siti; Rahmah Harahap Nur; Syafrida Handayani Luvi (BIO Web of Conferences)
This study aims to determine the effect of adding red dragon fruit peel extract in feed on the level of color brightness, growth, and survival of guppy fish. This study used a completely randomized design (CRD) method consisting of four treatments and four replications. The administration of dragon fruit peel extract was carried out by spraying it on the feed according to the treatment dose, including treatment A (0% or control), B (10% dose), C (15% dose), and D (20% dose). The results showed that the addition of dragon fruit peel extract with different doses had a significant effect on the brightness of the color of guppy fish (P <0.05). The highest color brightness value was obtained by adding red dragon fruit extract at a dose of 20% (treatment D) with a TCF value of 6.65. However, the administration of dragon fruit peel extract did not have a significant effect on the growth rate and survival rate of guppy fish (P>0.05). It can be concluded that red dragon fruit peel extract at a dose of 20% can be used as a natural pigmentation material in fish feed to increase the brightness of the color of guppy fish.